REFLEKSI NILAI-NILAI KEAGAMAAN PADA ARTIKEL REPUBLIKA “SILATURAHMI EDISI JULI 2016” - Wardah Hanafiah (Politeknik Negeri Jakarta, 2019)
AbstractThis study aims to determine the religious values contained in the text in the article entitled “Silaturahmi” which is published in the “Republika” online mass media in the “Khazanah Rubric”. These religious values are taught as part of the development of character education. Data is taken from article texts that contain good teaching values. This research is a qualitative research using content analysis method. Research data analysis techniques use triangulation. The research findings show that the religious values contained in the article entitled